The theological anthropology of Paulo Freire in Pedagogy of the Oppressed: a contribution to the discussion - Michael Attridge (Cadernos de História da Educação, 2023)
This paper explores the theological anthropology of Paulo Freire as found in the opening chapters of his Pedagogy of the Oppressed. It takes as its starting point that Freire was a Roman Catholic and a person of faith and that this is relevant to interpreting his work. It explores the roots and influences on him up until the 1960s. It points out that the existing literature neglects to consider the broader renewal of Catholic theology, particularly theological anthropology occurring in the twentieth century that found its way into Brazil through French catholic theologians. It concludes with an observation about how we might speak of the uniqueness of Freire’s theological anthropology.